2014
DOI: 10.1021/mp500108p
|View full text |Cite
|
Sign up to set email alerts
|

MMP-9 Responsive PEG Cleavable Nanovesicles for Efficient Delivery of Chemotherapeutics to Pancreatic Cancer

Abstract: Significant differences in biochemical parameters between normal and tumor tissues offer an opportunity to chemically design drug carriers which respond to these changes and deliver the drugs at the desired site. For example, overexpression of the matrix metalloproteinase-9 (MMP-9) enzyme in the extracellular matrix of tumor tissues can act as a trigger to chemically modulate the drug delivery from the carriers. In this study, we have synthesized an MMP-9-cleavable, collagen mimetic lipopeptide which forms nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
94
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(96 citation statements)
references
References 35 publications
2
94
0
Order By: Relevance
“…Furthermore, the amounts of the internalized Au gradually increased in proportion to the increase in amount of nanoclusters in the culture medium. Thus, these results strongly demonstrate that the internalization of the nanoclusters depends on the concentration of MMP-2, which suggests that the endocytotic behaviors of the nanoclusters depend on the overexpression of MMP-2 in tumor tissues [41][42][43].…”
Section: Accepted Manuscriptsupporting
confidence: 53%
“…Furthermore, the amounts of the internalized Au gradually increased in proportion to the increase in amount of nanoclusters in the culture medium. Thus, these results strongly demonstrate that the internalization of the nanoclusters depends on the concentration of MMP-2, which suggests that the endocytotic behaviors of the nanoclusters depend on the overexpression of MMP-2 in tumor tissues [41][42][43].…”
Section: Accepted Manuscriptsupporting
confidence: 53%
“…The number and location of the incorporated disulfide bonds allow fine-tuning of the release property from the vesicles. A typical composition that has been used widely for preparing redox-sensitive micelles [66] and liposomes [67] has been successfully implemented with polymersomes [8]. These copolymers contain a disulfide bond to connect the hydrophobic and hydrophilic polymers.…”
Section: Biomedically Translatable Polymersomesmentioning
confidence: 99%
“…At the tumor tissue, peptide cleavage destabilizes the drug carrier’s structure and releases the encapsulated contents. Overexpressions of matrix metalloproteinases [77,78] (MMP-9 and MMP-2), serine proteases and cysteine protease [79] (Cathepsin B) in tumor tissues have been utilized for designing enzyme-responsive polymersomes [26] and liposomes [67]. …”
Section: Biomedically Translatable Polymersomesmentioning
confidence: 99%
“…Hashida et al, and other groups have also reported on MMP based delivery systems. [44][45][46][47] Other proteases and enzymes, such as phospholipases 48) and glucose-oxidase, 49) have been utilized as stimulus triggers in drug delivery systems, too.…”
Section: Activation In Response To Endogenous/internal Stimulimentioning
confidence: 99%